Profiling with senescence-associated secretory phenotype score identifies GDC-0879 as a small molecule sensitizing glioblastoma to anti-PD1 - Yang Liu; Yuan Feng; Lin Cheng; Yangxi Xu; Anhua Wu; Peng Cheng (Cell Death and Disease)
Abstract Senescence-associated secretory phenotype (SASP) in cancer refers to the bioactive secretome produced by senescence cells in the tumor microenvironment, which could be triggered by therapeutics or local stress conditions. Here, we provided a SASP Score in glioblastoma (GBM) with generating a SASP gene panel to identify the potential small molecular candidate targeting SASP in GBM. The effectiveness of this scoring method was firstly interrogated with our in-house GBM cohort and public datasets, including transcriptomic data from bulk and single cell GBM samples. Then, we validate this score with functional assays and transcriptomic profiling of Doxorubicin-induced senescence GBM cells. Multi-omics profiling with this score demonstrates that SASP facilitates IDH wild type glioma progression by modulating both the behaviors of malignant cells and tumor associated macrophages (TAMs), and discloses GDC-0879 as a feasible SASP inhibitor in GBM therapy. Its administration not only attenuates the tumorigenicity of GBM cells, but also sensitizes GBM to anti-PD1 in preclinical mouse models. Together, we provide a SASP evaluation approach in glioma, and use it to highlight the critical role of SASP in GBM progression and demonstrate GDC-0879 as a small molecule impairing GBM tumorigenicity and improving their response to anti-PD1. Created by Figdraw ( www.figdraw.com ).